Geochronology of monazite related to REE, Nb–Ta and U–Th bearing minerals from Mesoproterozoic anorogenic magmatism in the E-Colombian Amazonian Craton: Links to mantle plume activity in the Columbia (Nuna) supercontinent. (August 2021) - Franco Victoria, Jose Alejandro; Cramer, Thomas; Chaves, Alexandre de Oliveira; Horn, Heinrich Adolf; Poujol, Marc
Abstract: U–Th–Pb geochronology of REE-bearing minerals such as monazite and other phosphates has become a precise tool to date mineralization events through geological time. In the E-Colombian Guainía department, from 3 colluvial sites over western Guiana Shield Mesoproterozoic rocks, Nb–Ta, U–Th and REE bearing minerals probably of pegmatitic origin were sampled including up-to-0.5 cm long monazite crystals. The monazite pan concentrate samples from sites near to the indigenous communities of Barranquilla, San Jose and Chorro Bocón (Espina hills) along the Cuyari, Guainía, and Inírida rivers respectively, were analyzed geochemically and geochronologically using LA-ICP-MS and EPMA. The monazites obtained from the 3 sites are rather similar with an approximate composition Ce0.44 La0.16 Nd0.16 Sm004 Y0.03 Gd0.02 Dy0.01 Pr0.05 Th0.08 Pb0.01 Ca0.05 Si0.05 P0.91 O3.94 . Their EPMA and LA-ICP-MS ages suggest at least two mineralization events, a first one between 1528 and 1523 Ma in the Barranquilla and San Jose sites, related to the emplacement of rapakivi granites outcropping along the Cuyarí River and the Tabaquen rapakivi granite near the Guainía River, both emplaced 1545 Ma ago. The second mineralization event from 1390 to 1343 Ma recorded in the Espina-hills is in the age range of the Matraca and Danta rapakivi granites that crystalized between 1400 and 1340 Ma ago. These different anorogenic rapakivi granites were emplaced between 1550 and 1300 Ma into Mesoproterozoic basement rocks and were probably caused by intra-plate processes associated with mantle plume activity within the Columbia (Nuna) supercontinent. Highlights: Discover of secondary deposits of ore minerals in Colombia eastern Region. First geochronological data for mineralization of Nb, Ta, REE and U–Th in NW Amazonian Craton. Ore mineral formation related to anorogenic magmatism during the Columbia (Nuna) supercontinent formation. Pegmatite formation related to Mesoproterozoic felsic intrusions in the western Guiana Shield. EPMA and LA-ICP-MS U–Pb monazite geochronology as a method for crystallization ages in pegmatites.